"No wasting" and "empty nesters": "Old age" in Beijing - Boermel, A (2006)
This paper explores the meaning of "old age" in reform-era Beijing from complementary perspectives. Based on extensive, multi-sited anthropological fieldwork and document analysis, it contrasts the experiences of older people in Beijing with a critical investigation of public debates about "old age". The paper examines older people's narratives about their gains and losses in the reform era and analyses several of their strategies to deal with rapid social change. It is argued that current debates about "old age" in Beijing tend to view older people as a collective, quantitative threat to the social structure or as pitiful recipients of rapid social change. Older people as active agents of social change are largely absent from these debates. It is suggested that the tension between public portrayals of "old age" by younger and middle-aged people and the experiences of older people is indicative of different, generation-based judgements of continuity and change in the reform era.